2021
DOI: 10.1021/acs.langmuir.1c00446
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Kinetics of Glycated Hemoglobin on Aptamer Microarrays with Antifouling Surface Modification

Abstract: Aptamers are oligonucleotides that bind with high affinity to target molecules of interest. One such target is glycated hemoglobin (gHb), a biomarker for assessing glycemic control and diabetes diagnosis. By the coupling of aptamers with surface plasmon resonance (SPR) sensing surfaces, a fast, reliable and inexpensive assay for gHb can be developed. In this study, we tested the affinity of SPR-sensing surfaces, composed of aptamers and antifouling self-assembled monolayers (SAMs), to hemoglobin (Hb) and gHb. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
(81 reference statements)
0
8
0
1
Order By: Relevance
“…Furthermore, due to a large amount of carbohydrates and protein in whole blood samples, the effective antifouling ability of the electrode can improve the affinity and specificity of detection. Duanghathaipornsuk et al [54] developed a gHb-targeted aptamer (GHA) through a modified SELEX process, and it was used to produce three distinct SAM-SPR-sensing surfaces with and without an antifouling layer. The results showed that the correlation between the HbA1c-targeted aptamer and HbA1c of the sensor surface with antifouling modification was higher than that of the sensor surface without modification, and the interference of nonspecific protein adsorption was reduced.…”
Section: Amperometric Sensorsmentioning
confidence: 99%
“…Furthermore, due to a large amount of carbohydrates and protein in whole blood samples, the effective antifouling ability of the electrode can improve the affinity and specificity of detection. Duanghathaipornsuk et al [54] developed a gHb-targeted aptamer (GHA) through a modified SELEX process, and it was used to produce three distinct SAM-SPR-sensing surfaces with and without an antifouling layer. The results showed that the correlation between the HbA1c-targeted aptamer and HbA1c of the sensor surface with antifouling modification was higher than that of the sensor surface without modification, and the interference of nonspecific protein adsorption was reduced.…”
Section: Amperometric Sensorsmentioning
confidence: 99%
“…Different research groups [ 103 , 104 , 105 ] have performed alternative selections of hemoglobin-binding DNA aptamers. However, these aptamers have been further used as biospecific elements for electrochemical, SPR, and fluorescent aptasensors with quite complicated analytical schemes and equipment [ 104 , 106 , 107 , 108 , 109 ], which can hardly be applied in routine clinical lab practice.…”
Section: Aptasensors For Biomarker Detectionmentioning
confidence: 99%
“…Non-specific attachment in SPR arrays has often been a critical problem that affects the reliability of assay results. To this end, Duanghathaipornsuk et al reported that the inclusion of 3,6-dioxa-8-mercaptooctan-1-ol (DMOL) in a self-assembled monolayermodified array surface can mitigate the nonspecific binding of proteins and impart more degrees of freedom to the aptamers for interacting with the targets [79]. In addition to sensing applications, SPR arrays can be used to assess the surface density of aptamer strands.…”
Section: Basic Spr Assaymentioning
confidence: 99%